The Relationship between Electricity Consumption and Economic Growth in Developing Countries: The Case of Turkey - Thorsten Mehltretter; Torsten Amelung (Kiel Institute of World Economics (IfW); ZBW - Leibniz Information Centre for Economics, 1986)
The paper analyses the link between electricity consumption and industrial and manufacturing output. The electricity sector plays a major role in the a development of a country, as there is a strong link between industrial power consumption and production. While this relationship, the so-called "iron link" is quite obvious on the aggregate level, the sectoral analysis came up with less a less stron correlation.
Keywords: Q43; Q48; 330; Public Investment in the Power sector; Impact on Economic Development